"Love's Not Time's Fool": Some Continuities, Discontinuities, and Alterations in Psychoanalysis During My Lifetime. Issue 1 (1st January 2018) - Kris, Anton O.
ABSTRACT: In this lecture the author reviews some important developments in North American psychoanalysis over the years since 1933. The most important of the changes is the recognition of the psychoanalyst as a participant in the analytic process rather than as an interpreter of unconscious meaning only. Beginning with some verbatim "interpretations" from the first recorded psychoanalysis in the 1930s, the lecture proceeds to consider a variety of topics, especially the importance of the relational tilt in U.S. psychoanalysis.